الحرمان من الخدمات الأساسية ودوره في انتشار ظاهرة الفقر وانخفاض مستوى المعيشة - صندوق عفيف; شريقي طرفة; غانم مي (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يعد الفقر من أكبر التحديات التي تواجه البشرية حالياً وهي بين أهم التحديات المستقبلية، ويعتبر ظاهرة بغاية التعقيد، ويهدف هذا البحث إلى التعرف على تأثير الحرمان من الخدمات الأساسية كخدمات الصحة والتعليم والمياه والصرف الصحي والكهرباء على الفقراء ودوره في انخفاض مستوى المعيشة، ومن خلال تصميم استبانة وجهت إلى عينة من الأسر من الفقراء غير الفقراء بين الريف والمدن، تضمنت المحاور التالية، مدى انتشار الخدمات الأساسية في المناطق، مدى استفادة الفقراء وغير الفقراء من هذه الخدمات، العدالة في توزيع تلك الخدمات، ومدى جودة ونوعية هذه الخدمات، وتم ربط هذه المحاور بالفقر وانخفاض مستوى المعيشة، وتم التوصل إلى أنه كان هناك علاقة طردية ضعيفة جداً بين الإنفاق الحكومي على الخدمات الأساسية وانخفاض معدلات الفقر، وكان هناك علاقة طردية ضعيفة بين تأمين الخدمات الأساسية للفقراء وتحسين مستوى المعيشة، وكانت العلاقة ضعيفة بين جودة الخدمة والحد من الفقر، وكان هناك علاقة طردية بين الإنفاق الحكومي وزيادة شريحة المواطنين المستفيدين. Poverty is one of the biggest challenges facing humanity , it is currently among the most important challenges of the future , and is a phenomenon of utmost complexity. The aim of this research is identify the impact of deprivation of basic services such as health , education, water , sanitation and electricity to the poor and his role in the decline in the standard of living , through the design of a questionnaire distributed among a sample of poor households both in rural and urban areas , which included the following points: the prevalence of basic services in the areas , the extent to which the poor and non-poor of these services , justice in the distribution of those services , and how the quality of these services , has been linked to these themes of poverty and low standard of living, Was reached the conclusions including there was a very weak positive correlation between government spending on basic services and lower rates of poverty, and there was a weak positive correlation between the provision of basic services to the poor and improving the standard of living, and the relationship was weak between quality of service and the reduction of poverty, and there was a positive correlation between government spending and increasing slice citizens beneficiaries.